2019
DOI: 10.3390/nu11020228
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tart Cherry Juice on Biomarkers of Inflammation and Oxidative Stress in Older Adults

Abstract: Inflammation and oxidative stress are important factors in the development of cardiovascular disease and atherosclerosis. The findings of our previous study suggest that 12 weeks consumption of tart cherry juice lowers the levels of systolic blood pressure (BP) and low-density lipoprotein (LDL) cholesterol in older adults. The present study investigated the effects of tart cherry juice on blood biomarkers of inflammation and oxidative stress. In this randomized-controlled clinical trial, a total of 37 men and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 50 publications
2
60
0
2
Order By: Relevance
“…tart cherry juice may be through its anti-oxidative and antiinflammatory properties. 30,32 This current investigation extends upon our recent study findings to explore the ability of tart cherry juice to improve subjective memory and cognitive function in older adults. Our present study demonstrated that 12 weeks supplementation of tart cherry juice increased subjective memory in the domain of contentment with memory by 5% and reduced movement time by 4% in comparison with the control drink.…”
Section: Figsupporting
confidence: 53%
See 4 more Smart Citations
“…tart cherry juice may be through its anti-oxidative and antiinflammatory properties. 30,32 This current investigation extends upon our recent study findings to explore the ability of tart cherry juice to improve subjective memory and cognitive function in older adults. Our present study demonstrated that 12 weeks supplementation of tart cherry juice increased subjective memory in the domain of contentment with memory by 5% and reduced movement time by 4% in comparison with the control drink.…”
Section: Figsupporting
confidence: 53%
“…Further, anthocyanin-rich supplements can inhibit tau hyperphosphorylation in the hippocampus and improve performance on cognitive behavioral tests as shown in mouse models of AD. 56 Our recent published studies 30,32 demonstrated that 12-week consumption of tart cherry juice lowered systolic BP by 4 mmHg and CRP by 25% as well as increased the plasma levels of DNA repair activity of OGG1. This supports the notion that the improvements in cognitive performance by tart cherry juice consumption may be due to its anti-inflammatory and anti-oxidative properties, and through a lowering of BP.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations